DEVELOPMENT OF TOURIST ATTRACTIONS AT THE DEPARTMENT OF CULTURE AND TOURISM OF PEKANBARU CITY - Wasiah Sufi; Dwi Herlinda; Elly Nielwaty (JURNAL SOSIO-KOMUNIKA, 2023)
This reseach Â examines development of tourist attractions at the department of culture and tourism of Pekanbaru City. The theory used is Cooper et al's theory from the book Kebijakan Pembangunan Destinasi Pariwisata, which states that a tourism destination development framework must have the following basic components: Objects and Attractions, Accessibility, Amenity, Supporting Facilities, and Institutions. This study employs qualitative research methodologies and is analyzed using qualitative descriptive methods. The findings of this study suggest that tourist attractions should be developed by attracting tourist attractions through upgrades and adjustments, as well as more sufficient amenities or facilities and infrastructure that exist in tourist attractions by providing guidance to the community. In addition, use the budget according to their needs to be sufficient.